Tracking Baltic hypoxia and cod migration over millennia with natural tags - Limburg, Karin E. (National Academy of Sciences, 2011)
Growing hypoxic and anoxic areas in coastal environments reduce fish habitat, but the interactions and impact on fish in these areas are poorly understood. Using “natural tag” properties of otoliths, we found significant correlations between the extent of Baltic Sea hypoxia and Mn/Ca ratios in regions of cod (Gadus morhua) otoliths corresponding to year 1 of life; this is associated with elevated bottom water dissolved manganese that increases with hypoxia. Elevated Mn/Ca ratios were also found in other years of life but with less frequency. We propose that cod exhibiting enhanced Mn/Ca ratios were exposed to dissolved manganese from hypoxia-induced redox dynamics in nursery areas. Neolithic (4500 B.P.) cod otoliths (n = 12) had low levels of Mn/Ca ratios, consistent with low hypoxia, but a single otolith dated to the younger Iron Age had a distinct growth band with an elevated Mn/Ca ratio. Sr/Ca patterns reflecting changes in environmental salinity and temperature were similar in both modern and Stone Age otoliths, indicating consistent migration habits across time, and Ba/Sr ratios in modern cod otoliths indicate increasing use of a more saline habitat with age. Using elemental ratios, numerous existing archival collections of otoliths could provide the means to reconstruct hypoxia exposure histories and major patterns of fish movement near “dead zones” globally.